P-203 Searching for the optimal timing of intracytoplasmic sperm injection post oocyte retrieval: a systematic review and meta-analysis. (30th June 2022) - Gupta, I; Thorrowgood, M; Ashton, K; Chapple, V; Liu, Y
Abstract: Study question: What is the optimal time post oocyte retrieval (POR) to undertake intracytoplasmic sperm injection (ICSI) in order to maximise subsequent pregnancy and live birth outcomes? Summary answer: Delaying ICSI for 5 hours or more POR may compromise subsequent clinical pregnancy and live birth rates. What is known already: It is often challenging to perform ICSI at a set timing POR, especially in ART clinics with a heavy workload. However, the degree of flexibility in ICSI timing remains unclear in the literature. Some articles have reported detrimental impacts by delaying ICSI on the subsequent treatment outcomes (Pujol et al 2018), while others reported no evidence of adverse effects caused by different ICSI timings (Vandenberghe et al 2021). Therefore, we aimed to explore a "safety time window" for ICSI procedures to enable flexibility in workflow arrangement without compromising pregnancy outcomes. Study design, size, duration: A systematic review and meta-analysis were performed according to PRISMA guidelines, with protocol registered with PROSPERO (ID: CRD42022296838). The studies were searched for in PubMed, MEDLINE, EMBASE and the Cochrane Library on 16 December 2021, using ("subfertile" OR "sub-fertile" OR "infert*" OR "fertility treatment" OR "women" OR "female" OR "couple") AND ("ICSI" OR "intracytoplasmic sperm injection" OR "intra-cytoplasmic sperm injection") AND ("timing" OR "time interval") AND ("pregnancy" OR "fertili*" OR "birth") NOT (Review [Publication Type]). Participants/materials, setting, methods: Two independent reviewers systematically evaluated each study on patient, intervention, comparison, and outcome (PICO). The Newcastle-Ottawa scale was used for risk of bias assessment in non-randomised trials and observational studies. Further screening was performed separately by the two independent reviewers, with differences mediated by the third reviewer. Data extraction was performed according to Cochrane methods. Clinical pregnancy or live birth data were synthesised from eligible studies depending on availability of raw data in corresponding subgroups. Main results and the role of chance: A total of 605 records were hit in the search. After initial exclusion according to PICO, 30 articles were included for further screening for eligibility. For meta-analysis, 4 retrospective cohort studies were eventually included for clinical pregnancy rate assessment while 2 for live birth rate analysis. Due to different groupings in ICSI timing amongst these studies, a series of comparisons on ICSI timings with a cut-off at an hourly increment were set up to pool data from the 4 included studies where applicable. Clinical pregnancy rates were comparable when ICSI was performed (a) 2+ hours (n = 6448, Relative Risk or RR = 1.031, 95% CI 0.964-1.102) in reference to < 2 hours POR (n = 2336), (b) 3+ hours (n = 5101, RR = 1.005, 95% CI 0.945-1.069) in reference to < 3 hours POR (n = 3465), and (c) 4+ hours (n = 3192, RR = 1.017, 95% CI 0.956-1.082) in reference to < 4 hours POR (n = 5374). However, clinical pregnancy rates were significantly compromised when ICSI was performed at 5+ hours (n = 2335, RR = 1.103, 95% CI 1.036-1.175) in reference to < 5 hours POR (n = 7169). Similarly, live birth rate was also significantly reduced when ICSI was performed 5+ hours (n = 2335, RR = 1.155, 95% CI 1.070-1.246) in reference to < 5 hours POR (n = 7169). Limitations, reasons for caution: All studies included for meta-analysis were retrospective with heterogeneity. There were various groupings amongst studies due to the wide range of ICSI timings POR, which limits data pooling and subsequent comparisons. A future well designed randomised controlled trial is warranted for further analysis based on better quality evidence. Wider implications of the findings: Our results indicate 5 hours POR should be considered the maximum time limit to perform ICSI. This finding, supported by statistics with improved power through meta-analysis, offers valuable guidance to busy clinics. This information could both improve pregnancy outcomes and allow better workflow arrangements without compromising them. Trial registration number: not applicable